Emergent Intentionality in Perception-Action Subsumption Hierarchies - Windridge, David (Frontiers in Robotics and AI, 2017)
A cognitively-autonomous artificial agent may be defined as one able to modify both its external world-model and the framework by which it represents world, requiring two simultaneous optimization objectives. This presents deep epistemological issues centered on the question of how a framework for representation (as opposed to the entities it represents) may be objectively validated. In this summary paper, formalizing previous work in this field, it is argued that subsumptive perception-action learning uniquely has the capacity to resolve these issues by a) building the perceptual hierarchy from the bottom up so as to ground all proposed representations and b) maintaining a bijective coupling between proposed percepts and projected action possibilities to ensure empirical falsifiability of these grounded representations. In doing so, we will show that such subsumptive perception-action learners intrinsically incorporate a model for how intentionality emerges from randomized exploratory activity in the form of 'motor babbling'. Moreover, such a model of intentionality also naturally translates into a model for human-computer interfacing that makes minimal assumptions as to cognitive states.